Basilar artery occlusion management: an international survey of gender influence on management - Peacock, Meabh; Drumm, Brian; Klein, Piers; Raymond, Jean; Huo, Xiaochuan; Chen, Yimin; Abdalkader, Mohamad; Schonewille, Wouter J.; Liu, Xinfeng; Hu, Wei; Li, Chuanhui; Ji, Xunming; et al. (Interventional neuroradiology, 2024)
Background - The superiority of endovascular thrombectomy (EVT) over medical management was not established in two early basilar artery occlusion (BAO) randomized controlled trials. Despite this, many clinicians recommended EVT for acute BAO under certain circumstances. This paper aims to compare physicians’ diagnostic and management strategies of BAO according to gender. - Methods - From January to March 2022 an international survey was conducted regarding management strategies in acute BAO. We compared responses between clinicians by identifying gender. Questions were designed to examine clinical and imaging parameters influencing management of patients with BAO. - Results - Among the 1245 respondents from 73 countries, 311 (25.0%) identified as female. This figure was 13.6% amongst interventionists. Geographically, female respondents were lowest in Asia (14.5%) and North America (23.9%). The proportion of respondents identifying as female was consistent regardless of their years of experience. Female respondents were more likely to choose time of onset as time of first estimated stroke like symptom (48.0% vs. 38.5%, p < .01), were less likely to favor thrombectomy in the V4 segment of vertebrobasilar artery occlusions (31.5% vs. 43.3%, p < .01), and were less likely to find it acceptable to enroll all patients who met trial criteria in the standard medical treatment arm of a clinical trial (41.2% vs. 47.0%, p = .01). Male respondents were more likely to agree that thrombolysis would not alter their decision on proceeding with EVT (93.7% vs. 88.3%, p < .01). - Conclusions - Female clinicians appear to be significantly underrepresented in stroke medicine. This is most pronounced amongst interventionists and in Asia. Although male and female opinions were closely aligned on many aspects of BAO management, differences in opinion were observed in a number of significant areas which influence decision making.
Gesehen am 01.07.2025